Disability management: The Insurance Corporation of British Columbia experience - Henry Harder; Leslie Potts (Pain Research and Management, 2003)
Insurance Corporation of British Columbia (ICBC) is a Crown Corporation created by the Provincial Government in 1974 to provide compulsory auto insurance. It is a common-law or tort system with 'add-on' no-fault provisions (medical/rehabilitation and disability benefits). ICBC insures 2 million British Columbia (BC) residents and pays out over $2 billion (Cdn.) in claims annually. One billion of this is for injury claims. Currently, one percent of these claims are catastrophic losses (paraplegic, quadriplegic, traumatic brain injury) with the remainder being non-catastrophic claims. Seventy percent of these non-catastrophic claims are soft tissue (primarily whiplash) injuries.